2020
DOI: 10.1111/jgs.16644
|View full text |Cite
|
Sign up to set email alerts
|

Facing Dementia During the COVID‐19 Outbreak

Abstract: We would like to thank team members Jaimie Roebuck and Andrea Lawson for their contribution to the preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
168
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(189 citation statements)
references
References 3 publications
(5 reference statements)
17
168
2
2
Order By: Relevance
“…However, these results provide us with insights into how to care for patients with dementia and how to efficiently use of the time and support of our limited staff during the COVID-19 outbreak. A previous study demonstrated that the COVID-19 outbreak adversely affected not only cognition and neuropsychiatric symptoms but also the functional independence of patients with dementia [1]. Therefore, our results indicate that for patients with moderate to severe cognitive impairment, it may be useful to prioritize prevention of their cognitive decline and maintenance of their functional independence, whereas for those with mild cognitive impairment, it may be useful to prioritize reducing psychological stress and preventing neuropsychiatric symptoms, such as depression.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…However, these results provide us with insights into how to care for patients with dementia and how to efficiently use of the time and support of our limited staff during the COVID-19 outbreak. A previous study demonstrated that the COVID-19 outbreak adversely affected not only cognition and neuropsychiatric symptoms but also the functional independence of patients with dementia [1]. Therefore, our results indicate that for patients with moderate to severe cognitive impairment, it may be useful to prioritize prevention of their cognitive decline and maintenance of their functional independence, whereas for those with mild cognitive impairment, it may be useful to prioritize reducing psychological stress and preventing neuropsychiatric symptoms, such as depression.…”
mentioning
confidence: 59%
“…Owing to the restrictive measures taken worldwide to block the spread of COVID-19 outbreaks (including the declaration of a state of emergency in Japan), patients with dementia and their caregivers have not been able to receive the usual support and care. Therefore, this is expected to lead to adverse effects on the patients and their caregivers, and many investigators have warned about the risks [1][2][3]. In fact, many scheduled appointments for routine outpatients' examinations and care services have been canceled and postponed owing to the COVID-19 outbreak.…”
mentioning
confidence: 99%
“…Some authors provide recommendations aiming to reduce behavioral dyscontrol in subjects with dementia in accordance with recommendations from dementia association guidelines, accounting for limitations caused the pandemic ( 24 ). Such guidelines stress implementation of technology to improve mood; maintain daily activities at home (e.g., gardening, cooking, reading, listening to music, physical exercise) to treat apathy; and foster the development of simplified and sequential routines to treat anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation may foster behavioral disturbances via several, partially overlapping mechanisms. Forced separation may interfere with caregiver support, whether the subject lives in his/her house or in nursing homes ( 24 ), and leads to poor health monitoring. Loss of interpersonal monitoring may increase the risk of dehydration, infections, and the decompensation of chronic diseases, such as diabetes or hypertension ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be due to the lack of mental stimulation, which is linked with levels of cognition in dementia (Woods, Aguirre, Spector, & Orrell, 2012). Recent early evidence into cognitive and behavioural symptomatology in dementia since the pandemic supports this notion (Boutoleau-Bretonni ere et al, 2020;Canevelli et al, 2020), posing a large concern for the increased care needs of PLWD. Increased levels of dependency became particularly difficult for those unpaid carers who suddenly had to take over care that was usually provided by paid carers.…”
Section: Discussionmentioning
confidence: 99%